Biorreator com membrana submersa para tratamento de esgoto de centros comerciais - Butzen, Everton Luis (2017)
Increased pressure on water resources demonstrates the need to create new strategies to improve water quality and conservation. The implementation of efficient sewage treatment using a combined acti vated sludge process with solid/liquid separation through membranes contributes to this water sustainability. The objective of this work is to evaluate the performance of submerged membrane bioreactor (SMBR) for the treatment of wastewater malls. The system was fed with samples collected at the University of Passo Fundo - UPF, without any previous treatment. The SMBR system operated with constant pressure and variable flow for the period of 60 days with sludge age maintained in 30 days. Total Suspended Solids (TSS) concentration wa s 3738±930 mg.L-1 and the mean flux obtained was 7.00±1.84 L.h-1.m-2. The characteristics of the raw sewage and the permeate were analyzed. The system presented great color removal and turbidity capacity, reaching average efficiency of 91.20% and 97.20%, respectively. The chemical oxygen demand (COD) removal average efficiency was 89.76% and for biochemical oxygen demand (BOD) it reached 87.78%, directly related to the SMBR biomass concentration, as well as the retention capacity of suspended solids and colloidal substances by the membrane. Phosphorus removal reached an average efficiency of 49.21%. The average efficiency in the removal of total nitrogen was 84.60% and of ammonia nitrogen 80.73%, with the occurrence of the nitrification process. The SBRM system proved to be an efficient process in the removal of the pollutants, remaining stable even with the oscillation of the characteristics of the raw sewage, presenting great potential for application in the treatment of sewage of shopping centers and in effluents with high organic loads.